High Levels of Epstein-Barr Virus DNA in Saliva and Peripheral Blood from Ugandan Mother-Child Pairs - Mbulaiteye, Sam M.; Walters, Michael; Engels, Eric A.; Bakaki, Paul M.; Ndugwa, Christopher M.; Owor, Anchilla M.; Goedert, James J.; Whitby, Denise; Biggar, Robert J. (The Journal of infectious diseases, 2006)
In Africa, Epstein-Barr virus (EBV) is associated with Burkitt lymphoma. We measured levels of EBV DNA in saliva and buffy coats from 233 asymptomatic Ugandan children with sickle cell disease and their mothers by quantitative real-time polymerase chain reaction. EBV DNA was detected in saliva from 90% of the children (median [interquartile range {IQR}] level, 5.2 [4.2–6.0] log10 copies/mL of saliva) and 79% of the mothers (median [IQR] level, 4.8 [3.7–5.6] log10 copies/mL of saliva) (P ! .001). EBV DNA was detected in buffy coats from 86% of the children (median [IQR] level, 2.5 [2.2–2.9] log10 copies/1 106 peripheral white blood cells [PWBCs]) and 72% of the mothers (median [IQR] level, 2.7 [2.4–3.1] log10 copies/1 106 PWBCs) (Pp.24). Detection of EBV DNA in saliva was positively correlated with detection in buffy coats. EBV DNA was detected more frequently in saliva and buffy coats than was human herpesvirus 8 DNA. Our results indicate that EBV infection persists, with virus readily detectable in saliva and buffy coats from persons without apparent symptoms in Africa.